Maternal feeding practices predict weight gain and obesogenic eating behaviors in young children: a prospective study - Rodgers Rachel F; Paxton Susan J; Massey Robin; Campbell Karen J; Wertheim Eleanor H; Skouteris Helen; Gibbons Kay (BMC, 2013)
Abstract Background Maternal feeding practices have been proposed to play an important role in early child weight gain and obesogenic eating behaviors. However, to date longitudinal investigations in young children exploring these relationships have been lacking. The aim of the present study was to explore prospective relationships between maternal feeding practices, child weight gain and obesogenic eating behaviors in 2-year-old children. The competing hypothesis that child eating behaviors predict changes in maternal feeding practices was also examined. Methods A sample of 323 mother (mean age = 35 years, ± 0.37) and child dyads (mean age = 2.03 years, ± 0.37 at recruitment) were participants. Mothers completed a questionnaire assessing parental feeding practices and child eating behaviors at baseline and again one year later. Child BMI (predominantly objectively measured) was obtained at both time points. Results Increases in child BMI z-scores over the follow-up period were predicted by maternal instrumental feeding practices. Furthermore, restriction, emotional feeding, encouragement to eat, weight-based restriction and fat restriction were associated prospectively with the development of obesogenic eating behaviors in children including emotional eating, tendency to overeat and food approach behaviors (such as enjoyment of food and good appetite). Maternal monitoring, however, predicted decreases in food approach eating behaviors. Partial support was also observed for child eating behaviors predicting maternal feeding practices. Conclusions Maternal feeding practices play an important role in the development of weight gain and obesogenic eating behaviors in young children and are potential targets for effective prevention interventions aiming to decrease child obesity.